The effect of slash and burn agriculture on plant nutrientes in the Tertiary Region of Central Amazonia - Brinkmann, W.L.F; Nascimiento, J.C. do (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
This work was carried out in an experimental area of ​​cacan near kvi 30 of the Manaus-Itacoatiava highway.